The development of student worksheets based on guided discovery with STEM-nuances to improve mathematical reasoning ability of class VII students - Tyas, Virga Rosa Arumning; Waluya, Stevanus Budi (Department of Mathematics, Universitas Negeri Semarang, 2021)
The research aims to develop student worksheets based on guided discovery with STEM-nuances to improve mathematical reasoning ability. The type of this research is Research and Development (R&D) by modification models from Sugiyono. The research was carried out through the analysis of potentials and problems, data collection, product design, validation, revision, product trial, and final product. The result of validity test show that student worksheets based on guided discovery with STEM-nuances to improve mathematical reasoning ability are valid with average score 4,67 and practical with average score 3,79. The analysis of pretest and posttest data showed that student worksheets effective to improve mathematical ability with the n-gain score 0,63 on medium category. Therefore, the student worksheets based on guided discovery with STEM-nuances to improve mathematical reasoning ability are valid, practical, and effective.